Spectrum of diffuse parenchymal lung disease with special reference to idiopathic pulmonary fibrosis: experience at Charlotte Maxeke Johannesburg Academic Hospital - Ndikundisani Ananius, Tshiovhe (My University, 2017)
Background Diffuse parenchymal lung diseases (DPLD) encompass a group of diseases with a wide range of causes with varied presentations and prognosis. The known causes include occupational or environmental exposure, drug induced lung diseases, hypersensitivity pneumonitis and connective tissue disease (CTD). Among the DPLD with unknown cause, idiopathic pulmonary fibrosis (IPF) is the commonest and has the worst outcome. The earlier publications from this country described cryptogenic fibrosing alveolitis. With subsequent characterisation of idiopathic interstitial pneumonia (IIP), and an increase in the burden of IPF reported worldwide, we evaluated the clinical features of patients with IPF in the South African context. Objectives To evaluate the clinical spectrum of DPLD encountered in Johannesburg, South Africa, and to describe the clinical profile of patients with IPF. Methods A retrospective record review of patient files was conducted who attended the Charlotte Maxeke Johannesburg Academic Hospital (CMJAH) Respiratory Clinic in the past 5 years from January 2011 to December 2015. Patients with DPLD were identified and the diagnoses were noted. The records of patients with IPF were further analysed. v Results We identified 132 patients with DPLD. Sarcoidosis (37.8%), IPF (21.2%), connective tissue associated diffuse parenchymal lung disease (CTD-DPLD) (14.3%), and hypersensitivity pneumonitis (HP) (9.8%) were the four most common subtypes. IPF was seen in all racial groups. Of the 28 patients with IPF in our cohort, there was a slight female predominance (1.3:1). The mean age of the patients in our study was 63.8 years and the majority were Whites. Cough (96.4%), dyspnoea (92.8%) and bilateral crackles (96.4%) were the commonest clinical features. The majority of patients (78.5%) were diagnosed by high resolution computerised tomography (HRCT) scan. Conclusion IPF is the second most common DPLD disease encountered after sarcoidosis at the CMJAH. IPF is seen in all racial groups in Johannesburg, South Africa, and the characteristics of patients with IPF are similar to those seen in other parts of the world.
A research report submitted to the University of the Witwatersrand, Johannesburg, in fulfilment for the requirements of the degree of Master of Medicine in Internal Medicine 2017
Keywords: Diffuse Parenchymal Lung Diseases; Idiopathic Pulmonary Fibrosis